Estimating social carrying capacity in protected Mediterranean mountain areas. Methodological orientation - Gómez-Moreno, María Luisa; Luque-Gil, Ana María; Peláez-Fernández, María Ángeles (My University, 2016)
The concept of social carrying capacity, though opens to debate and critique, is a valuable tool that enhances the management of recreational use in protected natural areas. In this study, conducted in Sierra de las Nieves natural park (Spain), we first categorised the hikers making use of the park and then, from the profiles obtained, analysed their perception of crowding on the trails. This assessment was subsequently used to assess levels of user satisfaction and thus to determine the psychosocial carrying capacity of the park. The results obtained can be extrapolated to most of the Spanish natural parks in Mediterranean mountain areas, due to their comparable levels of visitor numbers and to the prevalence of recreational hiking use. The results suggest that management efforts should be directed toward relocating trails outside the core areas, such that user preferences may be satisfied while less impact is made on the areas of highest environmental value.
Keywords: Excursionismo; Reservas naturales - Gestión; Hiking; Visitors classification; Natural area planning and management; Social carrying capacity